Altered distribution of I(Ca) impairs Ca release at the t-tubules of ventricular myocytes from failing hearts - Bryant, Simon M. (J Mol Cell Cardiol, 2015)
In mammalian cardiac ventricular myocytes, Ca influx and release occur predominantly at t-tubules, ensuring synchronous Ca release throughout the cell. Heart failure is associated with disrupted t-tubule structure, but its effect on t-tubule function is less clear. We therefore investigated Ca influx and release at the t-tubules of ventricular myocytes isolated from rat hearts ~ 18 weeks after coronary artery ligation (CAL) or corresponding Sham operation. L-type Ca current (I(Ca)) was recorded using the whole-cell voltage-clamp technique in intact and detubulated myocytes; Ca release at t-tubules was monitored using confocal microscopy with voltage- and Ca-sensitive fluorophores. CAL was associated with cardiac and cellular hypertrophy, decreased ejection fraction, disruption of t-tubule structure and a smaller, slower Ca transient, but no change in ryanodine receptor distribution, L-type Ca channel expression, or I(Ca) density. In Sham myocytes, I(Ca) was located predominantly at the t-tubules, while in CAL myocytes, it was uniformly distributed between the t-tubule and surface membranes. Inhibition of protein kinase A with H-89 caused a greater decrease of t-tubular I(Ca) in CAL than in Sham myocytes; in the presence of H-89, t-tubular I(Ca) density was smaller in CAL than in Sham myocytes. The smaller t-tubular I(Ca) in CAL myocytes was accompanied by increased latency and heterogeneity of SR Ca release at t-tubules, which could be mimicked by decreasing I(Ca) using nifedipine. These data show that CAL decreases t-tubular I(Ca) via a PKA-independent mechanism, thereby impairing Ca release at t-tubules and contributing to the altered excitation–contraction coupling observed in heart failure.